Effect of pore-forming agent quantity on pore structure, phase composition, micro-hardness of gradient bioceramic coatings under optimal laser process parameters. Issue 8 (1st June 2020) - Gu, Huaizhang; Fu, Qi; Sheng, Bo; Cai, Enpei; Tang, Geng; Liu, Qibin
Abstract: Titanium-based gradient bioceramic coating fabricated by laser cladding has been studied due to its excellent comprehensive performance and potential value in biomaterials. However, pore sizes of the coating prepared using traditional laser cladding technique are typically too small which can reduce its osteogenesis performance. To address this issue, a porous gradient bioceramic coating is successfully prepared on a titanium alloy surface by adding a pore-forming agent to the coating powder with subsequent laser cladding process. The bioceramic coating prepared with the optimized processing conditions (output power P = 1.8 kW, scanning speed V = 240 mm/min, and spot diameter D = 4 mm) exhibits a flat surface that comprises of a uniform enamel microstructure. The coating is metallurgically bonded to the substrate with a low number of microcracks. When the amount of pore-forming agent A = 2.5 wt%, the distribution of pores in coating becomes more uniform. When A = 2.5 to 10 wt%, the most probable pore size is 2.5 μm. It is shown that pore-forming agent quantity A = 2.5 wt% has a significant advantage in producing more large-sized pores in the coating. The number of pores in coating shows a trend of decreasing first, then increasing, and then decreasing. The coating phase consists of HA, β-TCP, TiO2, CaTiO3, etc., which is consistent with the coating material without pore-forming agent. In general, microhardness gradually decreases with increasing pore-forming agent quantity. The maximum microhardness values of coatings with and without pore-forming agent are 976 HV0.2 and 2086 HV0.2, respectively. Therefore, with the addition of a suitable amount of pore-forming agent, a porous bioceramic coating can be fabricated by an optimized laser cladding technique. This porous morphology will be beneficial for improving the osteogenic properties of the coating.